Origin, distributions, and environmental significance of ubiquitous humic-like fluorophores in Antarctic lakes and streams. (15th October 2019) - Kida, Morimaru; Kojima, Taichi; Tanabe, Yukiko; Hayashi, Kentaro; Kudoh, Sakae; Maie, Nagamitsu; Fujitake, Nobuhide
Abstract: This study characterized dissolved organic matter (DOM) obtained from 47 lakes and 2 streams on ice-free areas at Lützow-Holm Bay and Amundsen Bay in East Antarctica ( n  = 74), where few biogeochemical studies have been historically conducted. Samples were analyzed for basic water chemistry and by resin fractionation, UV–vis spectroscopy, and excitation emission matrix spectroscopy combined with parallel factor analysis (EEM-PARAFAC). Salinity of the samples ranged very broadly from fresh to hypersaline as a result of evaporative concentration. There was a clear positive correlation between log-salinity and the spectral slopes of DOM (S275–295 ), an indicator of photodegradation. Thus, we interpreted the correlation as a progression of photodegradation by prolonged water retention time. Of the identified seven PARAFAC components, three ubiquitous humic-like components decreased as photodegradation progressed, while a photorefractory UVC humic-like component increased its relative abundance. A non-humic component, traditionally defined as Peak N, did not show a trend depending on photodegradation, and its level was high in nutrient-rich lakes, presumably due to high in-situ production. We found robust correlations between the relative abundance of the ubiquitous humic-like components and that of the Peak N component in the bulk DOM irrespective of water types or ice-free areas. We proposed there were common processes that generated the ubiquitous humic-like components from the Peak N component in the Lützow-Holm Bay and Amundsen Bay lakes and streams, such as bacterial processing of primary production-derived DOM and photochemical transformation of microbial DOM. Highlights: Water chemistry and DOM composition of 47 Antarctic lakes and 2 streams were studied. Photodegradation substantially influenced the distribution of fluorescent DOM. Among seven PARAFAC components, four were humic-like components. Photochemical generation of ubiquitous humic-like fluorophores was proposed.